Influence of Permafrost Type and Site History on Losses of Permafrost Carbon After Thaw. Issue 11 (27th October 2021) - Manies, Kristen L.; Jones, Miriam C.; Waldrop, Mark P.; Leewis, Mary‐Cathrine; Fuller, Christopher; Cornman, Robert S.; Hoefke, Kristen
Abstract: We quantified permafrost peat plateau and post‐thaw carbon (C) stocks across a chronosequence in Interior Alaska to evaluate the amount of C lost with thaw. Macrofossil reconstructions revealed three stratigraphic layers of peat: (a) a base layer of fen/marsh peat, (b) peat from a forested peat plateau (with permafrost), and (c) collapse‐scar bog peat (at sites where permafrost thaw has occurred). Radiocarbon dating revealed that peat initiated within the last 2, 500 years and that permafrost aggraded during the Little Ice Age (ca. 250–575 years ago) and degraded within the last several decades. The timing of permafrost thaw within each feature was not related to thaw bog size. Their rate of expansion may be more influenced by local factors, such as ground ice content and subsurface water inputs. We found C losses due to thaw over the past century were up to 46% of the C available, but the absolute amount of C lost (kg m −2 ) was over 50% lower than losses previously described in other Alaskan peatland chronosequences. We hypothesize that this difference stems from the process by which permafrost aggraded, with sites that formed permafrost epigenetically (significantly later than most peat accumulation) experiencing less absolute C loss with thaw than sites that formed syngenetically (simultaneously with peat accumulation). Epigenetic peat from our site had lower C:N ratios as compared to Alaskan sites that have syngenetic peat. This difference could help predict the magnitude of C loss with thaw across a range or permafrost types and histories. Plain Language Summary: We quantified peat carbon at a permafrost peatland in Alaska to see how much carbon was lost from the peat when permafrost, or frozen soil, thawed and that area became a collapse‐scar bog. We found that size of the bog was unrelated to its age. Factors, such as the amount of ice in the soil and water entering the bogs from the surrounding forests, may have been more important in determining their growth. Carbon losses at our site were lower than carbon losses found from other Alaskan sites. We compared our results to other studies, some which had small losses of carbon due to thaw, others which found large losses. We found that factors related to time (i.e., age since peat initiation, number of years the site had permafrost) are important but do not fully explain these different results. However, when we include how permafrost formed we see a trend: sites where permafrost formed after peat (epigenetic permafrost) had smaller carbon losses than sites where permafrost and peats formed at the same time (syngenetic permafrost). Determining permafrost type can be difficult; instead scientists can use C:N ratios to determine if their samples resemble peat formed by epigenetic versus syngenetic permafrost. Key Points: Collapse‐scar bog ages at our sites were not related to feature size and may have been more influenced by local factors We found smaller losses of C with permafrost thaw than other studies from Interior Alaska The timing of permafrost aggradation relative to peat accumulation is an important factor in determining how much C is lost with thaw